Virtual Reality Immersion in Healthy Individuals: Ellipse Sway Area of an Electrical Shuttle Balance. Issue 3 (4th May 2021) - Coelho, Tarcísio Silva; Neto, Eduardo de Moura; Bazan, Rodrigo; de Souza, Luciane Aparecida Pascucci Sande; Luvizutto, Gustavo José
Abstract: To assess indirectly the effects of virtual reality (VR) immersion on postural sway in thirteen healthy individuals. The ellipse sway area was recorded with an accelerometer coupled to an electrical shuttle balance under six conditions, varying Romberg and single leg stance (SLS) position with eyes open and eyes closed. The length of the ellipse traveled over 10 s was measured and Romberg and single leg stance (SLS) ratios were calculated. Ellipse sway area was reduced in all positions after VR intervention. Statistical differences were observed in the left SLS ratio 24 hr after comparison to the baseline. A single VR session could reduce ellipse sway area and decrease the visual dependency of posture control indicating increased ability to maintain stable body sway over the shuttle.